Challenging Conventions—A Perspective From Within and Without - Green, Alison J. K. (Frontiers in Sustainability, 2021)
Academics globally are calling for urgent and proportionate action on the climate and ecological crisis (CEC), not only from governments and corporations but from leaders of academic institutions themselves. In this article, I argue that academic institutions are failing in their over-arching mission to humanity and the planet, and that they are increasingly part of the problem, not the solution. I explore the widespread use of league tables and metrics to capture and assess teaching and research performance and argue that these tell us little about how well academic institutions are faring in terms of their fundamental mission. I go on to chart the lackluster response of academic institutions to the CEC and a tendency to develop responses to the CEC that are centered on achieving carbon neutrality across estates and operations. I explore the moral and ethical case for transformative change within academia and give some examples of actions that institutions could readily take. The article concludes by stating that responsibility can no longer be shirked and that academic institutions must embrace Radical reform.